1998
DOI: 10.1056/nejm199810153391603
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Subthalamic Nucleus in Advanced Parkinson's Disease

Abstract: Electrical stimulation of the subthalamic nucleus is an effective treatment for advanced Parkinson's disease. The severity of symptoms off medication decreases, and the dose of levodopa can be reduced with consequent reduction in dyskinesias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
1,091
7
33

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,688 publications
(1,201 citation statements)
references
References 35 publications
57
1,091
7
33
Order By: Relevance
“…The improvement of both the motor score (UPDRS III) and the activities of daily living score (UPDRS II), was paralleled by an increase of the Schwab and England score up to 50 % six months after the surgical procedure which reflected the higher level of independence. These data are in accordance with recently published results from clinical studies [7,22,24,27].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The improvement of both the motor score (UPDRS III) and the activities of daily living score (UPDRS II), was paralleled by an increase of the Schwab and England score up to 50 % six months after the surgical procedure which reflected the higher level of independence. These data are in accordance with recently published results from clinical studies [7,22,24,27].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that the mean dosage of levodopa as well as the mean dosage of dopamine agonists could be reduced following DBS-STN [22,27]. Furthermore, one study reported that in nine out of ten patients the expensive treatment with apomorphine could be discontinued 12 months following continuous high-frequency stimulation [24]. Similar results were observed in our group of patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations